ANTECEDENTS AND CONSEQUENCES OF INTERNAL QUALITY OF PRODUCTS IN THE MANUFACTURING COMPANIES HOLDING SNI IN EAST JAVA - Rovilla El Maghviroh (Journal of Economics, Business, and Accountancy Ventura, 2010)
This study is a confirmatory study that was carried out by testing several hypotheses in order to figure out the causal relationship of all the stated variables. In attempt to such efforts, the study took the population of 205 manufacturing companies in East Java. All of them hold SNI (standard recognision of product). This study employed complete enumeration or census method; for that reason, the sample and sampling technique were not required. The technical analysis applied to test the research hypothesis was Structural Equation Modeling (SEM) with the support of Amos 5 program. The results of this research show that there are positive and significant relationship between communication level of objectives, frequency of feedback, effectiveness of incentive system of the quality on product internal and external quality and on change of financial performance. The benefit of this research is for scientific information regarding the variables of communication level of objectives, frequency of feedback, and effectiveness of incentive system of the quality on internal and external quality of product and on change of financial performance of the manufacturing companies in East java.